Determination of Natural and Artificial Radionuclides in Hot Water Spring Mud of Haymana-Ankara Spa (Turkey) - AKYUZ*, T.; VARINLIOGLU†, A.; KOSE†, A.; AKYUZ, S. (Asian Journal of Chemistry, 2009)
γ-Ray spectrometric analysis was performed on hot water spring mud samples, collected from Haymana-Ankara (Turkey) Spa, a well known health resort in the middle of Anatolia. The contents of natural and artificial radionuclides (226Ra, 235U, 238U, 228Th, 232Th, 40K and 137Cs) were determined. The results were compared with the radioactivity values of different Spas. γ-Isotopic analysis indicated that the maximum level concentration of the thermal mud samples for 226Ra, 235U, 238U, 228Th, 232Th, 40K and 137Cs were (Bq/kg) 162, 7.4, 156, 75, 127, 66 and 1.6, respectively.